A comparative study of intangible investment in Egypt and South Africa. Issue 3 (14th May 2018) - Chen, Wen
Abstract : Purpose: The purpose of this paper is to understand the recent developments and trends of intangible investment in Egypt and South Africa. Design/methodology/approach: This paper follows the framework pioneered by Corrado, Hulten and Sichel (2005, 2009) and measures investments in scientific R&D, organizational capital, and brand equity using the expenditure-based approach. Findings: The main findings are that South Africa invests consistently and considerably more in intangible assets than Egypt. Among the three intangible assets examined, namely, scientific R&D, organizational capital, and brand equity, South Africa seems to invest more evenly across these assets, whereas intangible investment in Egypt is predominantly driven by investment in brand equity and very little in R&D. Originality/value: This is the first paper to formally examine intangible investment in African countries. The ballpark estimate provided in this study is a useful step forward in understanding the trends of intangible investment in Egypt and South Africa.